"It's crucial they're treated as patients": ethical guidance and empirical evidence regarding treating doctor–patients. Issue 1 (21st December 2009) - Fox, F E; Taylor, G J; Harris, M F; Rodham, K J; Sutton, J; Scott, J; Robinson, B
Abstract : Ethical guidance from the British Medical Association (BMA) about treating doctor–patients is compared and contrasted with evidence from a qualitative study of general practitioners (GPs) who have been patients. Semistructured interviews were conducted with 17 GPs who had experienced a significant illness. Their experiences were discussed and issues about both being and treating doctor–patients were revealed. Interpretative phenomenological analysis was used to evaluate the data. In this article data extracts are used to illustrate and discuss three key points that summarise the BMA ethical guidance, in order to develop a picture of how far experiences map onto guidance. The data illustrate and extend the complexities of the issues outlined by the BMA document. In particular, differences between experienced GPs and those who have recently completed their training are identified. This analysis will be useful for medical professionals both when they themselves are unwell and when they treat doctor–patients. It will also inform recommendations for professionals who educate medical students or trainees.